1978
DOI: 10.1037/0022-3514.36.9.1054
|View full text |Cite
|
Sign up to set email alerts
|

Cross-situational consistency among problem adolescents: An application of the two-factor model.

Abstract: A study was conducted to measure cross-situational consistency of the orthogonal dimensions of the two-factor model of social-emotional functioning. According to this model, large proportions of variance in social-emotional functioning can be accounted for by two orthogonal, highly replicable dimensions. The setting was Hawthorne-Cedar Knolls, a long-term institution for emotionally disturbed and delinquent youths; the subjects were 206 residents of varied ethnic and socioeconomic backgrounds. Cross-situationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…First, as stated by Kenrick and Funder (1988), the behaviors or traits to be judged should be observable to permit reliability in ratings. Studies on the accuracy of personality judgments, using self-reports as a criterion and peer and stranger ratings as predictors, have generally found that observable traits and behaviors are more accurately judged than less observable ones (Albright et al, 1988;Funder & Colvin, 1988;Kenrick & Funder, 1988;Kenrick & Stringfield, 1980;Koretzky, Kohn, & Jeger, 1978;McCrae, 1982;Watson, 1989). Thus, traits such as extraversion and conscientiousness seem to be judged more accurately than traits such as emotional stability.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…First, as stated by Kenrick and Funder (1988), the behaviors or traits to be judged should be observable to permit reliability in ratings. Studies on the accuracy of personality judgments, using self-reports as a criterion and peer and stranger ratings as predictors, have generally found that observable traits and behaviors are more accurately judged than less observable ones (Albright et al, 1988;Funder & Colvin, 1988;Kenrick & Funder, 1988;Kenrick & Stringfield, 1980;Koretzky, Kohn, & Jeger, 1978;McCrae, 1982;Watson, 1989). Thus, traits such as extraversion and conscientiousness seem to be judged more accurately than traits such as emotional stability.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…This is the coefficient that Mischel (1968;but see Mischel, 1983) suggested was the typical upper limit of consistency across situations. The barrier was clearly breached by Koretzky et al (1978). They obtained correlations of .52 and .42 between two situations in the ratings by teachers and counselors of the behavior of problem adolescents on two higher order factors of social-emotional functioning.…”
mentioning
confidence: 98%
“…examine consistency between situations or raters, generally with a methodology that differs from Mischel's, (e.g., Epstein, 1979;Koretzky et al, 1978;Small et al, 1983). Secondly, there are those who argue for the consensual validity of traits by showing that subjects and their interactants agree about what the subjects are like.…”
mentioning
confidence: 99%
“…Indeed, he writes that the belief in personality traits comes about because of the perception of the stability in behavior (Mischel & Peake, 1982). For example, Koretzky, Kohn, & Jeger (1978), using independent raters, found moderate cross-situational consistencies in delinquents for apathetic (r = .42) and angry/defiant (r = .52) behaviors. For example, Koretzky, Kohn, & Jeger (1978), using independent raters, found moderate cross-situational consistencies in delinquents for apathetic (r = .42) and angry/defiant (r = .52) behaviors.…”
mentioning
confidence: 99%
“…For example, Koretzky, Kohn, & Jeger (1978), using independent raters, found moderate cross-situational consistencies in delinquents for apathetic (r = .42) and angry/defiant (r = .52) behaviors. One reason that rater judgments may show relatively high cross-situational consistency (e.g., Koretzky et al, 1978) is that raters base their judgments on a number of occasions. The low consistency found by Dudycha was based, however, not on ratings but on measurement of single responses.…”
mentioning
confidence: 99%